Catalytic performance of chars as catalyst for reforming pyrolytic tars from Shengli lignite pyrolysis - Wang, F.; Chen, Z.; Li, S.; Zhang, Shu; Wang, Y. (2013)
This study is to examine the in situ catalytic reforming of the coal tar derived from the pyrolysis of Shengli brown coal at slow an d fast heating rates in a fluidized-bed/fixed-bed quartz reactor. The catalysts (chars) were produced from pyrolysis of brown coal with and without the subsequent activation by steam. Besides the tar yields obtained from each experiment, the chemical composit ions of tar were further analyzed using GC-MS. It was found that the yields and compositions of tars from the slow and fast heatin g rates significantly varied. In the presence of catalysts (especially the activated char), the tar production dropped while the propor tion of large aromatic ring system in tar also significantly changed. The tar yields were generally decreasing with increasing reaction temperatures from 700 to 900 °C, but the increase in temperature changed the tar chemical compositions differently between slow and fast heating rates.